GENETIC DIVERSITY OF NATURAL POPULATIONS OF Bactrocera occipitalis (Bezzi) AND B. philippinensis Drew and Hancock (Diptera: Tephritidae) IN SELECTED MANGO PRODUCING AREAS IN THE PHILIPPINES USING MICROSATELLITES - Jalani, Grace Sheila; Laude, Rita; Diaz, Maria Genaleen; Medina, Celia; Velasco, Luis Rey (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2014)
Using nine microsatellite loci, the genetic diversity of natural populations of Bactrocera occipitalis and B. philippinensis was investigated. Estimates of genetic diversity based on allele number (na and ne), heterozygosity (Ho and He) and Shannon information index (I) revealed that the Cavite population was the most genetically diverse (na = 18.56; ne = 12.88; Ho = 0.58; He = 0.89; I = 2.55) and Pangasinan was the least (na = 7.89; ne = 8.94; Ho = 0.34; He = 0.87; I = 2.31). Among groups, the intermediates were the most genetically diverse (na = 25.44; ne = 15.30; Ho = 0.52; He = 0.92; I = 2.85) and B. philippinensis was the least (na = 17.44; Ho = 0.44; He = 0.90; I = 2.54). A low level of genetic diversity was detected among populations. Pangansinan and Palawan populations were the most related while Palawan and Guimaras populations were the least. Among groups, B. occipitalis and intermediates were the most related while B. occipitalis and B. philippinesis were the least. Dendrogram analysis indicated that B. occipitalis, B. philippinensis, and intermediates are not genetically distinct from each other.